Climate change and the oceans : gauging the legal and policy currents in the Asia Pacific and beyond - Warner, Robin; Schofield, Clive, (Political geographer) (Cheltenham, UK : Edward Elgar, 2012)
'Climate Change and the Oceans investigates the effects of climate change on the ocean environment and its implications for maritime activities, both globally and within the Asia Pacific region. This detailed work draws together informed opinion from a range of disciplines to examine the impacts of climate change on marine and coastal areas and review legal and policy responses to the rapidly changing ocean environment. Issues including the effects on fisheries and marine biodiversity in the Asia Pacific region, maritime security, global shipping, marine jurisdiction and marine geo-engineering are also explored. Examining the multiple impacts of climate change on the oceans and ocean based solutions to mitigate the adverse impacts of climate change, this thought-provoking book will prove invaluable to academics, researchers and students in the fields of law, environment, ecology and political science. Oceans and marine environmental policymakers will also find this to be an essential resource.'--Publisher.
Climate change and the oceans: legal and policy portents for the Asia Pacific region and beyond / Clive Schofield -- Implications of climate change for Asian-Pacific coastal and oceanic environments / Ove Hoegh-Guldberg -- Uncertain seas ahead: legal and policy approaches to conserving marine biodiversity in the face of changing climate / Robin Warner -- Climate change and marine living resources / Lisa Kirkendale -- Climate change : Antarctica and the Southern Ocean, science, law and policy / Marcus Haward -- Climate change and the limits of maritime jurisdiction / Andi Arsana -- Climate change and maritime security / Stuart Kaye -- The implications of climate change for maritime security forces / Chris Rahman -- Climate change and shipping / Stathis Palassis -- Climate change mitigation activities in the ocean: turning up the regulatory heat / Robin Warner.
Keywords: Ocean; Law of the sea; Climatic changes -- Environmental aspects